Inciting Protocols - How International Environmental Agreements Trigger Knowledge Transfers - Thijs Dekker; Herman R.J. Vollebergh; Frans P. de Vries; Cees A. Withagen (Tinbergen Institute, 2009)
This paper studies patenting decisions by firms in relation to the negotiation and signing of the Helsinki and Oslo protocol as part of the Convention on Long-Range Transboundary Air Pollution. We use a uniquely constructed patent data set on SO2 abatement technologies filed in 15 signatory and non-signatory countries in the period 1970-1997. The data distinguish between so-called 'mother' patents, or original inventions, and 'family' patents, which represent the same invention but are patentsfiled in foreign countries. Our analysis suggests that not only local environmental regulations matter for patenting decisions. International environmental agreements provide incentives for additional inventive activity in and the diffusion of knowledge towards signatory countries by reducing investment uncertainty for inventing firms.
Keywords: D7; D8; O31; Q5; 330; International environmental agreements; Inventions; Knowledge transfers; Patents; Acid rain; Saurer Regen; Internationale Umweltpolitik; Ökonomischer Anreiz; Wissenstransfer; Patent; Umwelttechnik; Welt